Exploring Muslim Perceptions of Apostasy and Religious Freedom in Islamic Law: An Empirical Study in Sri Lanka - Long, Ahmad Sunawari; Rufaida, Rajudeen Fathima; Saujan, Iqbal; Razick, Ahamed Sarjoon; Beevi, Hakeema (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Freedom of religion is a fundamental principle in the Universal Declaration of Human Rights (UDHR). However, some international human rights activists argue that Islam does not emphasize religious freedom. Despite this claim, historical accounts indicate that the prophetic tradition ensured religious freedom. While various studies have explored apostasy, they often overlook the perceptions of both Muslims and non-Muslims. Sri Lanka is a diverse country with multiple ethnic and religious groups and has experienced significant clashes over the years. Recognizing differences in views on apostasy among Muslims, this study examines their perceptions regarding religious conversion and its consequences in relation to Islamic legal norms derived from the Quran, Sunnah, and existing literature. The study focuses on the Kurunegala district, a region with a large pluralistic society. Using the Krejcie and Morgan sample selection table, 84 participants were selected, and self-administered questionnaires were used for data collection. The data were analysed using SPSS version 26. Additionally, research articles, books, and web publications were reviewed to construct a conceptual framework. The findings reveal that 78.9% of participants agree that Islam upholds religious freedom, while 16.1% disagree. A majority (78.5%) are unaware that Islam does not criminalize conversion under coercion, which contradicts Islamic teachings. Furthermore, 62.8% believe that individuals who convert from Islam to another religion should be punished, even if they do not harm the Muslim community. This study highlights the need to address misconceptions about apostasy among Sri Lankan Muslims, particularly in the Kurunegala district. It aims to contribute to strategies for reducing these perceptions and promoting a clearer understanding of Islamic teachings on religious freedom.